SMS-BASED SYSTEMS ACADEMIC SERVICES, FACULTY OF ENGINEERING, UNIVERSITY OF MATARAM - Widiartha, Ida Bagus Ketut (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
Academic information system of Faculty of Engineering, University of Mataram, has prepared academic data such as the grade of each course, Grade Point per Semester (GPS) and Grade Point Average (GPA). This needs to be equipped with class schedule, data of lecturers, assignment information and other announcements, as supporting the academic process, so that the system be comprehensively. On the other hand, the use of phonecell among academics of the Faculty of Engineering are already commonly used, some use more than one phonecell, as a means of communication and other purposes.For these reasons, in this study built SMS-based System for Academic Services that provide convenience to the academic community of the Faculty of Engineering, which obtain academic information and academic support through SMS. âSMS Requestâ will be served by a particular format, in order to authenticate users, the phone number should be registered firstly. In addition, the system service can be used by parents as a tool to monitor their children. The decision maker can also use this system to obtain valid information through SMS